Origin of the largest South American transcontinental water divide. Issue 1 (December 2018) - Ribeiro, Alexandre; Riccomini, Claudio; Leite, Jayme
Abstract Interbasin arches between hydrographic systems have a heterogeneous geological origin, forming under the influence of several different geomorphological processes. Independent of the underlying processes, these arches compartmentalize present-day river basins, encompassing different water chemistries, habitat types, soil domains, potential energy and, on a geological/evolutionary time scale, aquatic life varieties in the ecosystem. Through most of its length, the water divide between the Amazonian, Paraná-Paraguay, and São Francisco river basins in central South America coincides with an Upper Cretaceous intracontinental igneous alkaline province. This magmatism, independent of its nature, caused intense crustal uplift and influenced hydrological networks at different scales: from continental-scale crustal doming to continental break-up, and finally to local-scale phenomena. The available ages for alkaline rocks indicate a well-defined time-interval between 72.4 to 91 Ma (concentrated between 76 and 88 Ma) period of uplift that contributed to large-scale drainage compartmentalization in the region. Here we show that uplift associated with intrusive magmatism explains the origin and maintenance of the divide between the Amazonian, Paraná-Paraguay, and São Francisco river basins.